ANALISA KEPUASAN NASABAH TERHADAP LAYANAN CUSTOMER SERVICE BANK BUMN - Hilal Ubaidilah Nur (2022)
In the banking industry, customer service service the Bank BUMN provides (service excellence) customers to achieve customer satisfaction and loyalty. In its application, there are principles in the form of company standards to achieve service excellence success by this customer service. So the author is interested in researching the application of the principle of service excellence by customer service at the Bank BUMN. This research was conducted to determine the extent to which the implementation of service excellence by customer service at the Bank BUMN. In collecting data, the author uses a questionnaire method. Based on the results of the study, it can be concluded that the Bank BUMN customer service has been able to apply the principle of service excellence and the basic principles of excellent service which include Attitude, Attention, Action, Anticipation. Bank BUMN customer service can also handle obstacles in the application of the principle of service excellence so that customers feel satisfied and the services provided are optimal.